Michael Collins and the Anglo-Irish War : Britain's Counterinsurgency Failure - Hittle, J. B. E. (Book collections on Project MUSE., 2011)
As leader of the Irish Republican Brotherhood and then the Irish Republican Army (IRA), Michael Collins developed a bold, new strategy to use against the British administration of Ireland in the early twentieth century. His goal was to attack its well-established system of spies and informers, wear down British forces with a sustained guerrilla campaign, and force a political settlement that would lead to a free Irish Republic. This book reveals that the success of the Irish insurgency was not just a measure of Collins's revolutionary genius, as has often been claimed. British miscalculations, overconfidence, and a failure to mount a sustained professional intelligence effort to neutralize the IRA contributed to Britain's defeat. The author takes a fresh approach to the subject, presenting it as a case study in intelligence management under conditions of a broader counterinsurgency campaign. The lessons learned from this disastrous episode have stark relevance for contemporary national security managers and warfighters currently engaged in the war on terrorism. --from book description, Amazon.com.